TINGKAT KEMAMPUAN ASPEK PERKEMBANGAN NILAI AGAMA DAN MORAL ANAK DALAM BERMAIN PERMAINAN TRADISIONAL TAPO’ PIPIT - Lusi Ana; Halida Halida; Lukmanulhakim Lukmanulhakim; Ariyani Ramadhani (Jurnal Visi Ilmu Pendidikan, 2024)
This research aims to measure the improvement in aspects of the development of religious and moral values in children aged 5-6 years at the Primanda Untan Kindergarten through the traditional game tapo'pipit. This research is a type of quantitative descriptive research with an experimental method. The research subjects were children aged 5-6 years in group B2 with a total of 11 children from Primanda Untan Kindergarten. The data collection technique is observation technique with descriptive analysis. The results of the research show that there is an increase in children's ability to develop aspects of religious and moral values after playing the traditional game tapo'pipit. This is proven by the results of the frequency data obtained in the "Very Well Developing" category of 8 with a percentage value of around 83%- 100%. Furthermore, the "Developing According to Expectations" category is 3 with a percentage value of around 64% -83%.